COMPARATIVE EFFICACY OF COMBINED ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH MODERATE ARTERIAL HYPERTENSION ACCOMPANIED BY TYPE 2 DIABETES - E. I. Tarlovskaya; Yu. A. Balandina; I. E. Sapozhnikova; N. S. Maksimchuk (Рациональная фармакотерапия в кардиологии)
Aim. To compare efficacy of different fixed antihypertensive combinations in achievement of the target level of blood pressure (BP), to evaluate the dynamics of endothelium-dependent vasodilation (EDVD) and microalbuminuria (MAU) and to calculate cost-effectiveness ratio (CER). Material and methods. Patients (n=75) with moderate hypertension (HT) accompanied by type 2 diabetes (DM) were studied. The patients were randomized in groups A, B or C. Patients of group A (n=25) received a fixed combination of the original perindopril+indapamide, patients of group B (n=30) — a fixed combination of the generic enalapril+indapamide, patients of group C (n=20) — a fixed combination of the original enalapril+hydrochlorothiazide. Office BP was examined within the 4, 8 and 12 weeks, EDVD and MAU were determined initially and after 12 weeks of therapy. CER was also calculated. Results. The maximal antihypertensive effect was observed in group C (systolic BP (SBP) decreased in 46.6±1.3 mm Hg), followed by group A (SBP decreased in 43.1±0.8 mm Hg) and B (SBP decreased in 40.0±0.8 mm Hg). The groups were distributed as follows (in descending order): according to EDVD rise - group A (Δ4.52%), C (Δ3.14%) B (Δ3%); according to MAU prevalence rate reduction - group A (from 48% to 8%), B (from 40% to 23%) and C (from 40% to 25%). The “C” combination provided the lowest cost of BP reduction (12.33 rubles/mm Hg) and correction of MAU prevalence rate (1 514 rubles/case). According to EDVD improvement combination “A” had the lowest CER (2 805 rubles/case). Conclusion. According to pharmacoeconomic analysis the fixed combination of original enalapril+hydrochlorothiazide and the fixed combination of original perindopril+indapamide should be used in patients with moderate arterial hypertension, endothelial dysfunction and/or MAU.